A modified Lou-Huh model for characterization of ductile fracture of DP590 sheet. (15th March 2017) - Cheng, C.; Meng, B.; Han, J.Q.; Wan, M.; Wu, X.D.; Zhao, R.
Abstract: In this paper, a modified ductile fracture criterion was established to predict the fracture behavior of DP590 sheet based on Lou-Huh model. Considering the change of loading path during the plastic forming process, the C-H model was introduced to interpret the whole loading history. According to C-H model, the plastic loading process is divided into three stages including homogeneous deformation, deformation localization and localized instability. In addition, the variations of stress triaxiality and Lode parameter were tracked by the corresponding stress ratios under three tensile deformation patterns including uniaxial tension, plane strain tension and equi-biaxial tension. Based on the optimization algorithm, the material constants of the original and modified Lou-Huh fracture criteria were determined and their theoretical fracture limit strains were compared with the experimental one. Furthermore, the morphology of fracture surfaces was also taken to characterize the ductile fracture behavior of DP590 sheet. Results showed that the modified Lou-Huh model is more suitable for the prediction of ductile fracture of DP590 sheet, and the growth and shear coalescence of microvoids are correlated with stress triaxiality and Lode parameter, which change with the development of plastic deformation. Graphical abstract: Highlights: Constitutive model was built considering both uniaxial and equi-biaxial loading. Fracture criterion was derived considering material anisotropy and loading history. The prediction accuracy of FFLD was improved by the modified Lou-Huh model. Growth and coalescence of voids relate with stress triaxiality and Lode parameter.